2021
DOI: 10.1155/2021/8862025
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Cholinesterase Inhibitory and Antioxidant Activities of Enhydra fluctuans Relevant in the Management of Alzheimer’s Disease

Abstract: Enhydra fluctuans, a popular vegetable in Bangladesh, is used in folk medicine to treat diseases of the nervous system. The objective of this study was to investigate the phytochemical profile and cholinesterase inhibitory and antioxidant potential of the extracts of E. fluctuans. Among the four tested extracts, the chloroform extract was found to exert the highest inhibition against both the acetylcholinesterase and butyrylcholinesterase enzymes with the IC50 (concentration required for 50% inhibition) values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, AChE is reported as the major cholinesterase enzyme in the brain that catalyzes the hydrolysis of acetylcholine and shows higher specificity toward acetylcholine. Therefore, AChE enzyme has been an attractive target for AD therapy (26). In our study, P. galeata extract showed moderate inhibition against the AChE enzyme in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 50%
“…However, AChE is reported as the major cholinesterase enzyme in the brain that catalyzes the hydrolysis of acetylcholine and shows higher specificity toward acetylcholine. Therefore, AChE enzyme has been an attractive target for AD therapy (26). In our study, P. galeata extract showed moderate inhibition against the AChE enzyme in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 50%
“…It has previously been shown that a number of flavonoids can scavenge OH radicals [ 36 ]. Since free radicals have a detrimental role in Alzheimer’s disease progression, radical scavenging activities are crucial [ 37 ]. The present study indicates the half maximal inhibitory concentration (IC 50 ) values denoted the concentration of OPE required to scavenge 50% of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus antioxidants may be more effective to prevent and reverse AD progression ( Gezici et al, 2020 ; Veurink et al, 2020 ). Phenols and flavonoids are considered potential natural antioxidants having the ability to scavenge free radicals and reactive oxygen species because of their conjugated ring structures and OH group’s substitution ( Lopa et al, 2021 ). A study by Wang et al, 2014 suggested that treatment of the polyphenols combination resulted in improved protection against cognitive impairments in mice.…”
Section: Discussionmentioning
confidence: 99%